(untitled) (Bangladesh Journal of Medical Science, 2018)
Background and Objective: Qarahe Hazmiya (Peptic ulcer disease) is one of the commonest ailment of Gastro intestinal tract, reported to affect around 4% of the population and 10% of people developed it at some point in their life. Etiopathology of the disease is considered as multi factorial mostly treated with medications and rarely with surgery. Several Unani formulation have been indicated effective in Qarahe Hazmiya, one of such formulation has been selected to evaluate its efficacy and to validate the same on scientific parameters Methods: This study was conducted as a single blind, randomized standard control clinical trial on 28 patients (n=20) in test and (n=8) control groups. Test group received Ayarij Faiqura 5gm and control group received Pantoprazole 40 mg, orally in empty stomach for 45 days. The study outcome was assessed as the difference in pre and post treatment through subjective and objective parameters. Result: The test drugs revealed statistically significant improvement in burning sensation in abdomen (p<0.0001), pain abdomen (p<0.0001) as subjective parameters in comparison to control group where as objectivecally endoscopic report showed significantly improvement (p<0.0196) in comparison to control group with respect to the healing of ulcer / erosions. Interpretation and conclusion: The study revealed that the test drug had good response in controlling burning sensation and pain abdomen, along with healing of ulcer / erosions in comparison to control drug. No side effect or toxicity was observed during and or after the study. Thus, it could be concluded that the test drug was found to be safe and effective without any adverse effect. Bangladesh Journal of Medical Science Vol.17(1) 2018 p.112-117